(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Logical thinking has been seen as a skill that had to be improved in every educational context. Therefore, enhancing this ability has become a principal issue for many educators and researchers. A great deal of research has been carried out to reveal what fosters this ability and how it is fostered. In this article, the relationship between logical thinking and epic in the example of “Alpomish” epic is investigated. Hence the purpose of this article is to review the effects of epic on the learners’ logical thinking abilities. In addition, the implementation of epic in teaching process of comrehensive schools to enhance the logical thinking of learners is analyzed. Several activities that can be used in comprehensive schools to enhance the logical thinking of learners are proposed.